Intimate partner violence within Australian Defence Force families: an exploratory study. (1st June 2020) - Pollard, Rebecca; Ferguson, Claire
Abstract : International studies indicate a growing problem of intimate partner violence within military families. Despite this, there has been little research into intimate partner violence perpetrated by Australian Defence Force personnel or veterans. A thematic analysis of secondary data was conducted to explore the organisational and social drivers that influence intimate partner violence occurrences by Australian Defence Force personnel, and how the Australian Defence Force enforces its zero-tolerance policy on domestic violence perpetration. Results revealed that the Australian Defence Force and Department of Veteran Affairs made no statements regarding intimate partner violence as a problem for military personnel, despite this study indicating that this population are at a greater risk of perpetration. The Australian Defence Force attributed intimate partner violence causation to 'abnormal' individuals or situations. This ignores the culture of hypermasculinity and emphasis on operational effectiveness that was enforced during Australian Defence Force training, and that emerged as a continuous theme throughout the results.